LASSI-L detects early cognitive changes in pre-motor manifest Huntington’s disease: a replication and validation study - Luis A. Sierra; Shelby B. Hughes; Shelby B. Hughes; Clementina J. Ullman; Andrew Hall; Sarbesh R. Pandeya; Robin Schubert; Samuel A. Frank; Samuel A. Frank; Mark A. Halko; Mark A. Halko; Jody Corey-Bloom; et al. (Frontiers in Neurology, 2023)
Background and objectivesCognitive decline is an important early sign in pre-motor manifest Huntington’s disease (preHD) and is characterized by deficits across multiple domains including executive function, psychomotor processing speed, and memory retrieval. Prior work suggested that the Loewenstein-Acevedo Scale for Semantic Interference and Learning (LASSI-L)–a verbal learning task that simultaneously targets these domains - could capture early cognitive changes in preHD. The current study aimed to replicate, validate and further analyze the LASSI-L in preHD using larger datasets.MethodsLASSI-L was administered to 50 participants (25 preHD and 25 Healthy Controls) matched for age, education, and sex in a longitudinal study of disease progression and compared to performance on MMSE, Trail A & B, SCWT, SDMT, Semantic Fluency (Animals), and CVLT-II. Performance was then compared to a separate age-education matched-cohort of 25 preHD participants. Receiver operating curve (ROC) and practice effects (12 month interval) were investigated. Group comparisons were repeated using a preHD subgroup restricted to participants predicted to be far from diagnosis (Far subgroup), based on CAG-Age-Product scaled (CAPs) score. Construct validity was assessed through correlations with previously established measures of subcortical atrophy.ResultsPreHD performance on all sections of the LASSI-L was significantly different from controls. The proactive semantic interference section (PSI) was sensitive (p = 0.0001, d = 1.548), similar across preHD datasets (p = 1.0), reliable on test–retest over 12 months (spearman rho = 0.88; p = <0.00001) and associated with an excellent area under ROC (AUROC) of 0.855. In the preHD Far subgroup comparison, PSI was the only cognitive assessment to survive FDR < 0.05 (p = 0.03). The number of intrusions on PSI was negatively correlated with caudate volume.DiscussionThe LASSI-L is a sensitive, reliable, efficient tool for detecting cognitive decline in preHD. By using a unique verbal learning test paradigm that simultaneously targets executive function, processing speed and memory retrieval, the LASSI-L outperforms many other established tests and captures early signs of cognitive impairment. With further longitudinal validation, the LASSI-L could prove to be a useful biomarker for clinical research in preHD.